Low molecular weight hyaluronan induces migration of human choriocarcinoma JEG-3 cells mediated by RHAMM as well as by PI3K and MAPK pathways - Mascaró, Marilina (2017)
Hyaluronan (HA) is the major glycosaminoglycan present in the extracellular matrix. It is produced by some tumours and promotes proliferation, differentiation and migration among others cellular processes. Gestational trophoblastic disease (GTD) is composed by non-tumour entities, such as hydatidiform mole (HM), which is the most common type of GTD and also malignant entities such as choriocarcinoma (CC) and placental site trophoblastic tumour (PSTT), being CC the most aggressive tumour. Although there is a growing understanding of GTD biology, the role of HA in the pathogenesis of this group of diseases remains largely unknown. The aim of this work was to study the role of HA in the pathogenesis of GTD by defining the expression pattern of HA and its receptors CD44 and RHAMM, as well as to determine if HA can modulate proliferation, differentiation and migration of CC cells. Receptors and signalling pathways involved were also analyzed. We demonstrated that HA and RHAMM are differently expressed among GTD entities and even among trophoblast subtypes. We also showed that HA is able to enhance the expression of extravillous trophoblast markers and also to induce migration of JEG-3 cells, the latter mediated by RHAMM as well as PI3K and MAPK pathways. These findings indicate a novel regulatory mechanism for CC cell biology and also contribute to the understanding of GTD pathophysiology.